WORKLOAD ANALYSIS ON PUBLIC FUNERAL WORKERS IN PANDEMIC COVID-19 - Siti Azizah Hyaliti; Gita Aulia Nurani (JSSH (Jurnal Sains Sosial dan Humaniora), 2021)
This study aims to determine the level of the workload of public funeral officers during the pandemic in one city in Indonesia. The hypothesis in the study is that there has been an increase in the workload of public funeral officers since the surge in deaths due to Covid-19. The sampling technique used is non-random sampling in 25 people. This research method uses a mixed-method approach with inferential narrative data analysis techniques using SPSS software. The data processing results show that 44% of respondents fall into having a medium workload, and another 56% fall into the category of relatively high. External and internal factors cause the workload.